Measuring the Quality of Islamic Banks Services and Its Impact on Customers Satisfaction A Survey Study on the Islamic Banks Customers in Lattakia-Syria - Hammoud, Nashwa; Bittar, Mona (International Journal of Business, Economics and Management, 2016)
This study aims at exploring how Islamic banks’ customers assess the services provided to them and identifying the impact of the service quality' dimensions on customer satisfaction. To achieve the aims of this study, a convenient sample of the customers of Islamic banks branches in Lattakia- Syria is selected. Data are collected through a questionnaire designed on the basis of the service performance approach and compliance. Data analysis is conducted via the use of exploratory factor analysis, descriptive statistics, and regression analysis. The study concluded that the quality of the services provided by Islamic banks is high in general. However, the total scores of customer satisfaction indicated a moderate satisfaction. The results also showed a significant impact of all service quality dimensions on customer satisfaction with "Empathy" dimension being the most effective dimension.